Role of traditional Chinese medicine in age-related macular degeneration: exploring the gut microbiota’s influence - Yu, Yujia; Liu, Yong; Meng, Zhaoru (Frontiers in Pharmacology, 2024)
The pathogenesis of age-related macular degeneration (AMD), a degenerative retinopathy, remains unclear. Administration of anti-vascular endothelial growth factor agents, antioxidants, fundus lasers, photodynamic therapy, and transpupillary warming has proven effective in alleviating symptoms; however, these interventions cannot prevent or reverse AMD. Increasing evidence suggests that AMD risk is linked to changes in the composition, abundance, and diversity of the gut microbiota (GM). Activation of multiple signaling pathways by GM metabolites, including lipopolysaccharides, oxysterols, short-chain fatty acids (SCFAs), and bile acids (BAs), influences retinal physiology. Traditional Chinese medicine (TCM), known for its multi-component and multi-target advantages, can help treat AMD by altering GM composition and regulating the levels of certain substances, such as lipopolysaccharides, reducing oxysterols, and increasing SCFA and BA contents. This review explores the correlation between GM and AMD and interventions for the two to provide new perspectives on treating AMD with TCM.